Efeitos comparativos do Glutation (GSH) em dois modelos de solução preservadora do rim perfundido do coelho - Araujo Filho, Raimundo Messias (1995)
In order to evaluate relevant aspects related to organ preservation, renal parameters were examined in rabbit kidneys perfused “ex-vivo” either with Krebs- Henseleit solution, or with solution A, containing high potassium and magnesium concentrations. Glutathione(GSH) was added to the perfusate and its effects on renal functional parameters were also analysed. Addition of GSH to the perfusate in rabbit kidneys perfused with Krebs- Henseleit had no influence on the glomerular filtration rate and induced no metabolic benefit on fractional Na+ reabsorption, but a significant reduction of fractional K+ was obtained(p < 0,04). In kidneys perfused with solution A, lower glomerular filtration rates and decreased Na+ fractional transport were observed, as compared to Krebs- Henseleit perfused kidneys(p < 0,02). This pattern was also observed in kidneys perfused with different GSH concentrations. Despite high K+ concentrations of solution A, no difference was seen concerning K+ reabsorption, but a significant increase in free water clearance was noted in solution A perfused kidneys(p < 0,05). Addition of 4 mM to solution A induced higher Na+ reabsorption(p < 0,02) and an increase in osmolar clearance(p < 0,05). Addition of 4 mM GSH to solution A greatly enhanced Na+ reabsorption(p < 0,002) and also modified K+ transport. Although no effects of GSH addition to solution A were observed in distai function related free water clearance, osmolar clearance was significantly increased in this group(p < 0,05). Our results suggest that addition of GSH to the perfusate, either Krebs- Henseleit solution or solution A, has no influence on GFR, but enhances ions transport when a solution with high potassium and magnesium content is used.